Managing Beef Backgrounding Residual Soil Contaminants by Alum and Biochar Amendments. Issue 5 (1st September 2018) - Netthisinghe, A. M. P.; Cook, K. L.; Gilfillen, R. A.; Woosley, P. B.; Kingery, T.; Sistani, K. R.
Abstract : Heavy manure‐derived contamination of soils can make animal congregating areas nonpoint sources for environmental pollution. In situ soil stabilization is a cost‐effective management strategy with a focus on lowering contaminant availability and limiting release to the environment. Soil stabilizing amendments can help mitigate the negative environmental impacts of contaminated soils. In this 2‐yr study, we examined the effects of adding no amendment (control) or treating with alum [Al2 (SO4 )3 ⋅18H2 O] or biochar as soil amendments on Mehlich‐3 extractable soil P, Cu, and Zn contents, antimicrobial monensin concentrations, total bacteria (16S ribosomal RNA [rRNA] gene), antibiotic resistance genes ( sul 1 and erm B), and Class 1 integrons ( intI 1) in an abandoned beef backgrounding setting. The alum reduced soil P (1374 to 1060 mg kg −1 ), Cu (7.7 to 3.2 mg kg −1 ), and Zn (52.4 to 19.6 mg kg −1 ) contents. Both alum and biochar reduced monesin concentrations (1.8 to 0.7 and 2.1 to 1.1 ng g −1, respectively). All the treatments harbored consistent 16 S rRNA concentrations (10 9 copies g −1 ) throughout. The erm B gene concentration (10 5 copies g −1 ) was lower than either the sul 1 or the intI 1 genes (10 6 copies g −1 ), regardless of treatments. However, concentrations of all genes in the soils of animal congregation areas were higher than those in background soils with the least animal impact. In contrast with the effect on other contaminants, the effect of soil amendments on bacteria with antibiotic resistance genes was not biologically significant. Future research should be directed toward evaluating effective alternative methods to mitigate these bacterial populations. Core Ideas: The abandoned beef backgrounding soils contain high levels of residual contaminants. Alum effectively reduced environmentally significant soil nutrient concentrations. Both alum and biochar treatments lowered residual soil monensin concentrations. The amendment effects on antibiotic‐resistant genes were not biologically significant.